Participatory Communication Model Based on Local Wisdom in Ecotourism of West Detusoko Village - Bherta Sri Eko Murtiningsih; Niknik Meidiyawati; Veronika Veronika (Ikatan Sarjana Komunikasi Indonesia, 2024)
Sustainable ecotourism development needs participation, participatory communication, and local wisdom. A participatory communication strategy needs to be implemented so that the community is willing to accept the policy and get Â involved in developing and maintaining these tourist destinations. Communication must be dialogical and symmetrical, and decision-making must be participatory by considering local wisdom. This study uses participatory communication theory. The study uses a qualitative approach with a case study method. Data collection uses literature studies, in-depth interviews, and FGDs. Informants in the study were selected using a purposive sampling technique. The research findings show that participatory communication in ecotourism planning and development includes Dialogue, Heteroglossia, Polyphony, and Carnival. Meanwhile, the model of community participation is empowered participation. Ecotourism based on local wisdom can increase community participation and build participatory communication. Optimizing ecotourism based on local wisdom can help increase people's income and maintain nature conservation and cultural preservation.